Risk and Benefit Analysis of China’s Foreign Direct Investment in the Energy Sector: Case Study of the Belt and Road Initiative - Kovalova, Erika; Vartiak, Lukas (International Journal of Economics and Financial Issues, 2024)
Since 2011, China has been the world’s largest energy consumer. The industrial sector uses two-thirds of the energy consumed in China. The main reason for investment in energy is that China is a net importer of energy, especially oil. The impact of Chinese foreign investments and the energy sector, which is the largest of the individual sectors, are the main subjects of the analysis of the presented paper. In the paper, we used the WoS viewer program to perform a bibliometric analysis of authors, countries, and keywords that deal with FDI. Subsequently, we used various scientific methods, such as the method of observation, method analysis, synthesis, comparison, exploration and explanation, to analyse Chinese investments that flow into multiple sectors worldwide, but especially into the countries participating in the Belt and Road Initiative and into the energy sector from 2013 to the present. As part of the Belt and Road Initiative, China invests in various projects in the form of "loans" and, in many cases, creates debt traps that allow China to seize the assets of participating countries. In this paper, we focused on the energy sector and its development so far within the given initiative, and we also defined what the initiative should focus on within renewable resources. China’s energy investments include oil, hydropower, alternative energy, natural gas, and coal. The sharp drop in Chinese investment after 2019 was caused by the COVID-19 pandemic. To conclude, although energy has remained China’s primary sector for investment within the BRI regions, Chinese capital has gradually diversified into sectors such as transportation, real estate, technology and innovation, and tourism.